Intentional partial beaching in a coral reef fish: a newly recorded hunting behaviour of titan triggerfish, Balistoides viridescens. Issue 5 (27th September 2020) - Tietbohl, Matthew D.; Hardenstine, Royale S.; Tanabe, Lyndsey K.; Hulver, Ann Marie; Berumen, Michael L.
Abstract: Coral reef fishes use a multitude of diverse feeding behaviours to increase their ability to successfully capture a wide range of prey. Here, this study reports a novel hunting behaviour in a coral reef fish, the titan triggerfish, Balistoides viridescens, where an individual was seen partially beaching itself while attempting to catch a Red Sea ghost crab, Ocypode saratan . This is the first report of this behaviour in the order Tetraodontiformes and represents an astonishing capability of this species to exploit food resources outside their typical assumed ecological niche.